2022
DOI: 10.3390/catal12020181
|View full text |Cite|
|
Sign up to set email alerts
|

Green Synthesis of TiO2 Nanoparticles Using Acorus calamus Leaf Extract and Evaluating Its Photocatalytic and In Vitro Antimicrobial Activity

Abstract: Here, we present an innovative and creative sustainable technique for the fabrication of titania (TiO2) using Acorus calamus (A. calamus) leaf extract as a new biogenic source, as well as a capping and reducing agent. The optical, structural, morphological, surface, and thermal characteristics of biosynthesized nanoparticles were investigated using UV, FTIR, SEM, DLS, BET, and TGA-DSC analysis. The phase formation and presence of nanocrystalline TiO2 were revealed by the XRD pattern. FTIR analysis revealed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 55 publications
5
18
0
Order By: Relevance
“…This The nitrogen adoption-desorption isotherms of the GKT are shown in Figure 4a,b. The isotherm was similar to the IUPAC type-IV classification, which indicated the existence of a mesoporous structure [44][45][46]. Table 1 shows the surface area, pore volume, and pore size of the GKT.…”
Section: Physico-chemical Characterizationsupporting
confidence: 57%
“…This The nitrogen adoption-desorption isotherms of the GKT are shown in Figure 4a,b. The isotherm was similar to the IUPAC type-IV classification, which indicated the existence of a mesoporous structure [44][45][46]. Table 1 shows the surface area, pore volume, and pore size of the GKT.…”
Section: Physico-chemical Characterizationsupporting
confidence: 57%
“…They claimed the best results with 5% of material after 30 days. In another study reported by Ansari et al [ 62 ], the antimicrobial activity of material prepared from leaf extracts was tested. They demonstrated that the maximum efficiency was achieved after 24 h against common bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The wide range of inorganic NP uses arises from their distinct physicochemical and biological characteristics, including their small size to the large surface area, high surface energy, a large fraction of surface atoms, reduced imperfections, spatial confinement, surface plasmon light scattering, surface plasmon resonance (SPR), surface-enhanced Rayleigh scattering, surface-enhanced Raman, and scattering (SERS) properties [ 18 , 19 ]. Many reports have shown the ability of several plant parts, including the leaves, roots, stems [ 20 ], seeds [ 21 ], flowers [ 22 ], and others, to synthesize various controlled shapes and sizes of inorganic NPs that incorporate silver [ 20 ], gold [ 20 ], platinum [ 23 ], palladium [ 24 ], and metal oxides such as titanium oxide [ 25 ], iron oxide [ 26 ], copper oxide [ 27 ], etc. These green NPs exhibit potent biological activity against pathogenic bacteria, such as Streptococcus pneumoniae causing meningitis [ 28 ], Klebsiella pneumoniae causing pneumonia and bloodstream infections [ 29 ], Escherichia coli causing urinary tract infections [ 30 ], and Staphylococcus aureus causing infective endocarditis and osteoarticular infections [ 31 ].…”
Section: Introductionmentioning
confidence: 99%